INVESTIGAÇÃO DA PRESENÇA DE Bartonella spp. EM DOADORES DE SANGUE NO ESTADO DO RIO DE JANEIRO - VALTER DOS SANTOS CUENCA (2021)
Bartonella spp. are fastidious, difficult to isolate, Gram-negative proteobacteria. Bartonella spp. infect erythrocytes and endothelial cells, and can cause asymptomatic infections with severe morbidity, including potentially fatal conditions in humans. Accidental transmission to man occurs by inoculation of the bacteria after trauma, bites, or scratches from infected animals, or by hematophagous arthropod vectors (sand flies, fleas, lice, biting flies, ticks, and potentials triatomines). This study analyzed the prevalence of Bartonella spp. in blood donors from the reference blood center in the state of Rio de Janeiro, Brazil. This is a cross-sectional study with primary data. Peripheral blood was collected by donor convenience sampling in 2018. The study was approved by the Research Ethics Committee (CEP) of HEMORIO (No. 409/16), and an epidemiological questionnaire was given to participants donors. Serum sample was analyzed for the presence of IgG against Bartonella henselae, using the Bartonella henselae IFA IgG kit (Focus, USA) by Indirect Immunofluorescence Reaction (RIFI). Of the 501 blood donor samples, 12% (60/501) were positive for IgG anti B. henselae, with a cut-off titer of 64. Among seroreactive donors, 18 (30%) were female and 42 (70%) were male; aged between 18 and 65 years (mean age 37.48 years), all residents of the metropolitan region of the state of Rio de Janeiro, with the majority from the municipality of Rio de Janeiro (41 or 68.3%). There were no statistical significances (p≤ 0.05) in chi-square test, between being seropositive for Bartonella and gender, Ethnicity, exposure with vectors, contact with animals and age. The conventional polymerase chain reaction (PCR) technique with 3 specific primers, namely, the citrate synthase protein gene (gltA), the heat shock protein gene (htrA) and the gene encoding the beta subunit of RNA polymerase (rpoB). Were used to test the blood donors samples the presence of DNA Bartonella in the bloodstream was detected in 0.2% (01/501) of donors only in the gltA initiator. PCR the sequence obtained showed 100% similarity to Bartonella henselae. The results of the study indicate serological evidence of Bartonella henselae in blood donors in the state of Rio de Janeiro and it is necessary the inclusion of Bartonella spp. in the list of agents of transfusional transmission during routine screening of blood donors.